Iowa Birdlife - Black, Gladys (Book collections on Project MUSE., 1992)
From robins nesting on window ledges to short-eared owls sailing low over snowy fields, pied-billed grebes diving for fish to catbirds singing on moonlit nights, Black introduces us to the birds of field and forest, prairie and pond. Whether describing red-breasted nuthatches gorging on suet at her feeder after a snowstorm or a flock of American goldfinches ""all balancing gracefully on ripening oats, ' she reminds us of the natural sights and sounds that we must appreciate and protect. Humorous, personal, engaging, and instructive, her essays provide a readily acessible body of information a.